Physioeconomic Poverty Analysis of Grade 1 Employees of Rawalpindi City, Pakistan - Siddiqui, Sabeen; Anwar, Zubair; Batool, Saira; Habib, Nusrat; Naheed , Sobia; Zahra, Naheed (Asian Journal of Agriculture and Rural Development, 2014)
Poverty though a universal phenomenon, is the worst challenge in the modern era, which is termed as the age of information and technology. The present study was designed to estimate the incidence of poverty for the grade I employees of Rawalpindi city. Determinants of poverty were explored by using Probit model, which was significant in the determination of the poverty status of the household. Following variables were used in the model; household size, education, experience, working individual, extra income and migration are the variables. For that objective, data from 150 household were collected through questionnaires. The results of the poverty indices showed that about twenty percent households were poor among grade 1 employees of Rawalpindi city. The result of probit models indicated that having large household size, with no extra income and migrants were increasing the probability of being poor while educational attainment and experiences did not had significant effect. On the other hand working individuals and migration were decreasing the probability of being poor.